24‐hour movement behaviors and fitness in preschoolers: A compositional and isotemporal reallocation analysis. (10th March 2021) - Lemos, Luís; Clark, Cain; Brand, Caroline; Pessoa, Maria Luíza; Gaya, Anelise; Mota, Jorge; Duncan, Michael; Martins, Clarice
Abstract : This study analyzed the associations between the 24‐hour movement behaviors composition and fitness in preschoolers and investigated predicted changes in fitness when time in active behaviors is reallocated. This cross‐sectional study was carried out with 270 preschoolers (132 boys; 3.97 ± 0.80 years‐old). Light and moderate‐to‐vigorous physical activity (LPA and MVPA), and sedentary behavior (SB) were verified using an accelerometer. Sleep time was obtained through interviews with parents. Components of physical fitness (cardiorespiratory fitness—CRF, speed‐agility, and lower‐body muscular strength) were assessed using the PREFIT Battery. To verify the association between 24‐hour movement behaviors and physical fitness, the compositional analysis was used, and for the time reallocation, the compositional isotemporal substitution analysis was used for active behaviors (LPA and MVPA). The daily composition, adjusted for body mass index, sex, and age, was significantly associated with CRF ( P  = .007; r 2  = 0.29), speed‐agility ( P  < .001; r 2  = 0.14), and lower‐body muscular strength ( P  = .01; r 2  = 0.07). For CRF, the addition of MVPA, at the expense of any other behavior, was associated with significant improvements. For speed‐agility and lower‐body muscular strength, only reallocations between sleep and LPA yielded significant associations. The variation in CRF, speed‐agility, and lower‐body muscular strength was associated with the 24 hours movement composition, and reallocating 5, 10 or 15 minutes of SB or sleep for MVPA was significantly positive for CRF ( P  < .05). The present findings highlight the relevance of decreasing SB and increasing physical activity practice, particularly at high intensities, to promote a better CRF profile for preschoolers.